Generic Relationships of Zygopetalinae (Orchidaceae: Cymbidieae): Combined Molecular Evidence - Whitten, Mark; Williams, Norris; Dressler, Robert; Gerlach, Günter; Pupulin, Franco (Lankesteriana: International Journal on Orchidology, 2015)
The phylogenetic relationships of the orchid subtribe Zygopetalinae were evaluated using parsimony analyses of combined DNA sequence data of nuclear ITS 1 and 2 (including the 5.8s region and portions of the flanking 18s and 26s regions) and of the plastid trnL intron plus the trnL-F intergenic spacer and the plastid matK. Analyses of the three separate data sets produced highly congruent and moderately supported patterns, so these were combined in a single analysis. Combined analysis of 104 ingroup and two outgroup taxa produced highly resolved cladograms. Zygopetalinae comprises a Zygopetalum grade or clade (pseudobulbs prominent; leaves usually plicate, revolute); a Huntleya grade (pseudobulbs reduced or lacking; leaves conduplicate), including Dichaea, Huntleya, Chaubardia, and the Chondrorhyncha complex, plus Cryptarrhena that is weakly supported as sister to the Huntleya clade; and a Warrea grade. Chondrorhyncha s.l. is polyphyletic and six genera are here segregated as monophyletic taxa (see Key words).